44 IPU or ITU? It all starts with PCT (palliative care training). (13th October 2019) - White, Nicola; Minton, Ollie; Oostendorp, Linda; Stone, Patrick
Abstract : Background: Impending death is not well recognised.1 Due to improvements in technology and medicine, people are living longer with more complex health conditions2 and because of this, the death of a patient is an experience that many people entering a healthcare profession will have little of. As death occurs in any setting, at any time, it is vital that all healthcare professionals regardless of the setting they go on to work in, have adequate Palliative Care Training (PCT). Aim: To understand what current training is available on the recognition of dying at undergraduate level. Methods: An information gathering exercise of the following UK undergraduate courses: medicine, nursing, social work, physiotherapy, occupational therapy. All courses received an email asking what training was provided in recognising and communication of dying and what time was dedicated to this. Results: 73/198 courses responded (37%). 18/20 medical courses provided training in recognising dying with a median of 2 hours dedicated, and 17/20 in the communication of dying with a median of 3 hours dedicated. 80% (43/54) of nursing and allied health professional courses provided some form of training in end-of-life care. Many of these courses expressed frustration at the lack of resources, funding, and time to include more training. Those with more time dedicated to PCT often had a 'champion' to advocate for it. Conclusion: Training in end-of-life care was inconsistent and variable across courses and professions. Further work on how we can support the champions in progressing PCT input on the courses is needed.